COVID-19: Scientific overview of the global pandemic (2020)
COVID-19 (Coronavirus Disease 2019) is the disease caused by the novel Coronavirus, SARS-CoV-2. Genome sequence of the virus revealed that it’s a new zoonotic virus which might have evolved by jumping from bats to humans with one or more intermediate hosts. The immediate availability of the sequence information in public domain has accelerated development of quantitative-reverse-transcription PCR based diagnostics. Besides, numbers of clinical trials have been prioritized globally for testing new vaccines and treatments against this disease. This review gives a broad insight into different aspects of the COVID-19 disease, introduction to SARS-CoV-2, mitigation strategies, present status of diagnostics and therapeutics.